Habilidades sociais acadêmicas de crianças com baixo e alto desempenho acadêmico na interação com o professor - Fumo, Vivian Maria Stabile (2009)
Identifying the features related to the quality of teacher-student interaction and to the set of teacher and student s social skills is a key aspect for a more accurate understanding of learning difficulties. Studies show qualitative differences in the pattern of social interactions established by children with low and high academic performance with their teachers. However, due to small numbers of participants, those results might not be generalized. The main goal of this study was to identify behavioral patterns of students with low and high academic performance in the social interaction with the teacher, from academic social skills classes, investigating how the likely qualitative differences in patterns of interaction was an extended sample of participants. 41 students with low academic performance (GSLAP) and 44 students with high academic performance (GSHAP) from first to fourth grades, attending to Public Elementary Schools, participated in this research. It was performed shootings of the classroom environment to collect the data about behavioral patterns of students in the social interaction with the teacher. Children´s pattern of social skills were evaluated by the Social Skills Rating System (SSRS-BR) in the version of self-assessment and evaluation by the teacher. The shootings were analyzed through observations of the academic social skills classes. The SSRS-BR s results were analyzed according to criteria established by instrument. Data analysis included descriptive and inferential statistics. Concerning to academic social skills, main results were: (a) there were differences between academic social skills classes show more frequently by GSLAP and by GSHAP; (b) a few number of academic social skills classes shown statistically significant differences about gender and academic subject; (c) no academic social skills classes shown statistically significant differences about grade. The main results about social skills were: (a) GSHAP obtained mean performance in the selfassessment and in the evaluation by the teacher; (b) GSLAP obtained mean performance in the self-assessment and obtained lower than the mean performance in the evaluation by the teacher; (c) in the self-assessment and in the evaluation by the teacher there were not statistically significant differences about grade in the GSLAP and in the GSHAP; (d) there were statistically significant differences about gender in some SSRS-BR s scores in the GSLAP and in the GSHAP. Results show a difference between the behavioral patterns of students with low and high academic performance in the interaction with the teacher, and differences between the patterns of social skills of these two groups. Though these differences might not be stated as critical to their academic difficulties, they certainly might not be ignored as a condition that aggravates the possibilities of development of students in the school.